1986
DOI: 10.3382/ps.0650164
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification of Commercial Linseed Meal for Use in Broiler Rations

Abstract: A method for the detoxification of commercial deoiled linseed meal was standardized that involved water boiling of powdered meal and subsequent removal of water solubles by centrifugation. The hot-air dried sludge was evaluated for its possible use as a protein supplement in broiler chick rations. Growth studies of chicks showed that water-boiled linseed meal at 50% protein replacement level was superior to, and at 75% protein replacement level was on par with, the control diet based on expeller pressed ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…A marked rise in GOT activity is indicative of organ damage and would provide evidence of Cu toxicosis per se. Failure of dietary Cu to affect SGOT activity, indicated that Cu toxicosis per se was not occurring, and although SN supplementation resulted in increased SGOT activity, levels were well within normal ranges reported in the literature (Dalvi and McGowan, 1984;Madhusudhan et al, 1986). It is concluded that the reduction in performance observed in this study was primarily due to a copper-mediated reduction in feed intake and not to copper toxicosis per se.…”
Section: Discussionsupporting
confidence: 72%
“…A marked rise in GOT activity is indicative of organ damage and would provide evidence of Cu toxicosis per se. Failure of dietary Cu to affect SGOT activity, indicated that Cu toxicosis per se was not occurring, and although SN supplementation resulted in increased SGOT activity, levels were well within normal ranges reported in the literature (Dalvi and McGowan, 1984;Madhusudhan et al, 1986). It is concluded that the reduction in performance observed in this study was primarily due to a copper-mediated reduction in feed intake and not to copper toxicosis per se.…”
Section: Discussionsupporting
confidence: 72%
“…The increase in liver weight at high levels of CBC might be an attempt by the organ to detoxify theobromine containing diets. Antinutritional factors have been associated with the enlargement of organs like liver and pancreas (Madhusudhan et al, 1986).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that the linolenic acid content of poultry meat and eggs can be increased through increasing the n-3 fatty acid content of poultry diets (Caston and Leeson, 1990;Hargis and Van Elswyk, 1993;Bond et al, 1997). However, flaxseed contains some antinutritional fac-tors that had been reported to decrease performance of birds depending on the dietary levels and form of the plant (whole seed, oil extracted) used in the diet (Madhusudhan et al, 1986;Lee et al, 1991).…”
Section: Introductionmentioning
confidence: 99%